IL-6 signaling in acute exercise and chronic training: Potential consequences for health and athletic performance - Nash, D.; Hughes, M. G.; Butcher, L.; Aicheler, R.; Smith, P.; Cullen, T.; Webb, R. (Scandinavian Journal of Medicine & Science in Sports, 2023)
The cytokine interleukin-6 (IL-6) is involved in a diverse set of physiological processes. Traditionally, IL-6 has been thought of in terms of its inflammatory actions during the acute phase response and in chronic conditions such as rheumatoid arthritis and obesity. However, IL-6 is also an important signaling molecule during exercise, being acutely released from working muscle fibers with increased exercise duration, intensity, and muscle glycogen depletion. In this context, IL-6 enables muscle-organ crosstalk, facilitating a coordinated response to help maintain muscle energy homeostasis, while also having anti-inflammatory actions. The range of actions of IL-6 can be explained by its dichotomous signaling pathways. Classical signaling involves IL-6 binding to a cell-surface receptor (mbIL-6R; present on only a small number of cell types) and is the predominant signaling mechanism during exercise. Trans-signaling involves IL-6 binding to a soluble version of its receptor (sIL-6R), with the resulting complex having a much greater half-life and the ability to signal in all cell types. Trans-signaling drives the inflammatory actions of IL-6 and is the predominant pathway in disease. A single nucleotide polymorphism (rs2228145) on the IL-6R gene can modify the classical/trans-signaling balance through increasing the levels of sIL-6R. This SNP has clinical significance, having been linked to inflammatory conditions such as rheumatoid arthritis and type 1 diabetes, as well as to the severity of symptoms experienced with COVID-19. This review will describe how acute exercise, chronic training and the rs2228145 SNP can modify the IL-6 signaling pathway and the consequent implications for health and athletic performance.